Application of concentrated growth factors in reconstruction of bone defects after removal of large jaw cysts – The two cases report - Mirković, Siniša; Djurdjević-Mirković, Tatjana; Puškar, Tatjana (Vojnosanitetski pregled, 2015)
Introduction. Coagulation and blood clot formation in bone defects is sometimes followed by retraction of a blood clot and serum extrusion, thus producing peripheral serum-filled spaces between bony wall and coagulum. This can result in a higher incidence of postoperative complications. Stabilization of blood coagulum, which enables successful primary healing, may be accomplished by autotransplantation, allotransplantation, xenotransplantation, or application of autologous platelet concentrate and concentrated growth factors (CGF). Case report. Two patients with large cystic lesions in the upper and lower jaw were presented. In both patients postoperative bony defects were filled with autologous fibrin rich blocks containing CGF. Postoperative course passed uneventfully. Conclusion. Application of fibrin rich blocks containing CGF is one of the possible methods for reconstruction of bone defects. CGF can be applied alone or mixed with a bone graft. The method is relatively simple, without risk of transmissible and allergic diseases and economically feasible.
Keywords: jaw cysts; oral surgical procedures; platelet-derived growth factor; transplantation; autologous